Deconstruction of Penal System Policy on Tax Law in Indonesia against Liability for Corporate Income Tax Evasion - Annika Rahmawati (PT Publikasiku Academic Solution, 2024)
The purpose of this study is to simplify legal policies in the Law on General Provisions and Tax Procedures by the values of Pancasila in technical and its implementation in the application of law and law implementation in tax crimes. Normative juridical research methods are processed qualitatively and descriptively, using sources of legal materials